Word Class Conversion And Its Benefits In The EFL Context - Teofanne Nurinik Wea; Barli Bram (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
One way to increase learners’ skills and the language’s elements is through the word formation process, especially conversion. This study aimed to investigate types of word conversion in the Oxford English Dictionary (OED), and the implications of word conversion for the EFL context. This study was a descriptive qualitative study, and the researcher used morphological analysis in analyzing the data. In gathering the data, the researcher accessed the website of the Oxford English Dictionary and tried to search the word conversion between Noun-Verb, Verb-Noun, and adjective-verb. The result of the study showed that 227 words were included in word conversion. Those words consisted of 104 noun-verb conversions, 12 noun adjectives, 55 adjective-nouns, and 56 verb-nouns. Furthermore, as demonstrated by previous studies, word conversion can improve learners’ skills, especially in reading, writing, and speaking. It is also crucial in learning the elements of language, such as grammar and vocabulary.